DIAGNOSTIC YIELD OF IMAGE GUIDED CORE BIOPSY AND FINE NEEDLE ASPIRATION CYTOLOGY IN THE EVALUATION OF VARIOUS MASSES: Diagnostic Yield of Image Guided Core Biopsy - Qayyum, Abdul; Ilyas, Muhammad; Fayyaz, Afshan; Iqbal, Omar (Pakistan Armed Forces Medical Journal, 2009)
Objective: The purpose of this study is to evaluate diagnostic yield of ultrasound / computed tomography (CT) – guided core biopsies and fine needle aspiration cytology (FNAC) of various masses. Study Design: An observational study. Place and duration of study: This study was carried out in radiology department of Combined Military Hospital Rawalpindi from Aug 2006 to May 2007. Patients and Methods: A total of 91 patients with wide range of masses involving different organs of body underwent image guided core biopsies and FNAC. Sixty seven patients were males and 24 were females. Age of patient ranged from were performed under ultrasound guidance. Out of the 91 cases, 48 were core biopsies and 43 FNAC. Biopsies were performed with 18G Monopty gun and FNAC were done with 20 – 22G lumbar puncture (LP) needle in all cases except FNAC of thyroid gland, cervical lymph nodes and calf muscle (in which FNAC was done with 5cc disposable syringe). Results: Out of 48 core biopsies, 40 (83.3%) had adequate diagnostic yield and histopathologist was able to give a definite diagnosis. However in 8 (16.7%) biopsies, diagnostic yield was inadequate and it was labelled non-diagnostic by histopathologist. Similarly out of 43 FNAC, 33 (76.7%) had adequate diagnostic yield and 10 FNAC (23.3%) were declared non-diagnostic. Over all success rate was found to be 80.22%. Conclusion: Image guided core biopsies and FNAC, both are very helpful in histophatological diagnosis of various masses and success rate is quite high when appropriate technique is employed.